2018
DOI: 10.3892/etm.2018.6342
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cells inhibit metastasis of ovarian carcinoma cells and show therapeutic effects in a murine model of ovarian cancer

Abstract: Ovarian cancer has the highest mortality rate and is the most common of all gynecologic malignancies. Novel treatments for ovarian cancer are urgently required to improve outcomes and the overall survival of patients. The present study investigated whether immunotherapy with natural killer (NK) cells affected the survival of mice with ovarian cancer. Results analysis identified adjunctive NK cells as a potential therapeutic method in ovarian cancer. Patient-derived ovarian cells were isolated, cultured and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Upon unraveling the epidemiologic association between NK cells and cancer [24], research efforts ensued to use NK cells in the treatment of cancer via adoptive cellular transfer. In both in vitro and in vivo studies, NK cells have been shown to mediate direct killing of human cancer cells in acute myeloid leukemia, acute lymphoblastic leukemia, multiple myeloma, glioblastoma, neuroblastoma, Ewing sarcoma, rhabdomyosarcoma, melanoma, and carcinomas of the breast, lung, ovary, colon, pancreas, renal cells, and stomach [17,30,31,32,33,34,35,36].…”
Section: Low Nk Cell Activity and Cancer Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon unraveling the epidemiologic association between NK cells and cancer [24], research efforts ensued to use NK cells in the treatment of cancer via adoptive cellular transfer. In both in vitro and in vivo studies, NK cells have been shown to mediate direct killing of human cancer cells in acute myeloid leukemia, acute lymphoblastic leukemia, multiple myeloma, glioblastoma, neuroblastoma, Ewing sarcoma, rhabdomyosarcoma, melanoma, and carcinomas of the breast, lung, ovary, colon, pancreas, renal cells, and stomach [17,30,31,32,33,34,35,36].…”
Section: Low Nk Cell Activity and Cancer Developmentmentioning
confidence: 99%
“…Early trials have been conducted in advanced cancer patients with a high tumor burden. In those studies, signs of clinical response were observed as was indicated by preclinical models that NK cell therapy prevented migration and invasion of cancer cells contributing to prevention of systemic metastasis [36]. However, such response was not dramatic as it did not meet the expectation of the scientific community.…”
Section: Strategies To Enhance the Effect Of Nk Cell Therapymentioning
confidence: 99%
“…In preceding studies, the antitumour effects were reported by injecting 10 6 NK cells twice or single injection of 10 7 cells to a mouse. 32 , 33 No toxic effects were mentioned in both reports, suggesting that NK cells of 2 × 10 6 –10 7 cells per mouse can exert antitumour effects without toxic phenotypes. In addition, we observed no apparent tumour formation in 15 weeks after the last injection of the treated NK cells (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Several studies have shown the following effects of NK cells in different cancers: NK cells have been shown to be effective in patients with advanced lung cancer; Herceptintreated NK cells have been found to have therapeutic potential in the treatment of patients with human epidermal growth factor receptor 2 (Her2 + ) and Herceptin-intolerant breast cancer; expanded and cryopreserved NK cells are promising candidates for cellular immunotherapy in patients with pancreatic carcinoma; NK cells inhibit metastesis of ovarian carcinoma cells in murine models; CIK cells may become a novel therapeutic modality for rhabdomyosarcoma after allogeneic HSCT; CAR-engineered CIK cells may become valuable in the treatment of HR soft tissue sarcoma in children; and expanded and CIK cells are safe and well tolerated and they enhance cytotoxicity against gastric carcinoma [162,[265][266][267][268][269][270][271]. A meta-analysis, that included 29 clinical trials involving 2610 patients, has been shown that the combination of CIK/DC-CIK immunotherapy and cytotoxic chemotherapy: enhances the immune function of patients, alleviates the adverse effects of chemotherapy, and improves the overall response, disease control, and quality of life [272].…”
Section: Nk Cells In Solid Tumorsmentioning
confidence: 99%